A Comparative Study of Absorbing Layer Methods to Model Radiating Boundary Conditions for the Wave Propagation in Infinite Medium - Shankar Badry, Ravi; Kotti, Maruthi; Kumar Ramancharla, Pradeep (International Journal of Engineering and Technology, 2018)
Radiating boundary condition is an important consideration in the finite element modelling of unbounded media. Absorbing layer techniquessuch as Perfectly Matched Layers (PML) and Absorbing Layers by Increasing Damping (ALID) becoming popular as they are efficient in absorbing outward propagating waves energy. In this study, a comparative analysis has been carried out between PML and ALID+VABC (Absorbing Boundary conditions for Viscoelastic materials) methods. The methods are analyzedusing LS-DYNAexplicit solver and the efficiency is compared with standard solutions.The study concluded that PML requires less number of elements to model the boundary conditions when compared with ALID+VABC. But PMLrequires a smaller element length which increases overall computational time. Both the methods are efficient in absorbing the wave energy. However, PML requires additional implementation cost to solve the complex equations.Â